Effect of elastic abdominal binder on pain and functional recovery after caesarean delivery: a randomised controlled trial - Wisit Chankhunaphas (2019)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. The Elastic abdominal binder has been widely employed by clinicians for pain relief, wound complications prevention, improved pulmonary function, and stabilisation. However, these proposed benefits have not been properly examined in women following caesarean delivery. We aimed to examine the effects of post-caesarean elastic abdominal binder use on recovery by comparing post-operative pain, mobility and quality of life. Pregnant women undergoing caesarean delivery were randomly assigned into two groups: abdominal binder (90 patients) and control (90 patients). The primary outcomes included the daily visual analogue scale pain scores and the distance from the six-minute walk test. Baseline characteristics were similar between the groups. There was no significant difference in pain scores and six-minute walking distance between the study groups. There was no significant between-group difference in quality-of-life dimensions, overall health status, and post-operative complication. The positive effects of elastic abdominal binder use following caesarean delivery could not be demonstrated in this study.Impact statementWhat is already known on this subject? Elastic abdominal binder is commonly used after laparotomy to support incision. There was evidence to support the benefit of abdominal binder in reducing psychological distress during the first five days following laparotomy for other indications. From limited number of studies addressing caesarean section, the evidence for the benefits of the binder on pain, symptom distress, and change in haemoglobin level is conflicting. What do the results of this study add? In contrast to the results of the previous study, the beneficial effects of abdominal binder on pain reduction, functional recovery, and quality of life following caesarean delivery could not be demonstrated in this study. What are the implications of these findings for clinical practice and/or further research? The use of elastic abdominal binder after caesarean delivery is not associated with reduction of postoperative pain, faster functional recovery, and improved quality of life in our population. Further studies in other population with different characteristics may be worthwhile.